Changing the electronic health record to optimize pre-chemotherapy lab orders. Issue 28 (1st October 2022) - Lam, Barbara; Celmen, Melis; Graham, Tim; Dechen, Tenzin; Zerillo, Jessica Ann
Abstract : 434 Background: National guidelines support screening for infectious diseases and pregnancy before starting cancer-directed treatment. Providers also check liver and kidney function to ensure safe medication dosing. Forgetting to order these tests has implications for patient safety and treatment area throughput. Our aim was to modify the provider order entry (POE) screen in the electronic health record (EHR) to reduce missed laboratory orders for hepatitis B, pregnancy tests, and organ function.Methods: We revised the hematology/oncology POE screens so that labs were grouped by organ system rather than listed alphabetically. A new Pre-Treatment Screening (PTS) order set includes urine pregnancy and a hepatitis B panel. We collected retrospective ordering data at our medical center's ambulatory academic and community sites from the pre-intervention (10/20 – 9/21) and post-intervention (10/21 – 4/22) time periods. Data was analyzed to determine the pre/post change in percentage of add-on chemistry tests, rate of ordered urine pregnancy and hepatitis B tests in new patients, and proportion of positive hepatitis B tests. Results: There were 165, 360 total chemistry lab orders pre-intervention and 91, 948 post-intervention. The percentage of add-ons decreased from 0.50% (834/165, 360) to 0.38% (351/91, 948). There were 1, 109 pre-intervention new treatment starts (92/month) and 673 post-intervention (96/month). The rate of hepatitis B screening increased from 86/month to 99/month and the rate of urine pregnancy testing remained the same at 4/month. The proportion of positive hepatitis B surface antigen tests increased from 0.72% (8/1109) to 0.89% (6/673). The proportion of positive hepatitis B core antibody tests decreased from 9.83% (109/1109) to 9.51% (64/673). Conclusions: Simple changes to an electronic ordering screen were associated with increased adherence to pre-treatment screening guidelines. Further PDSA cycles are needed to explore what changes to POE can optimize appropriate utilization of lab orders, especially for pregnancy screening. This has far-reaching consequences not only for new chemotherapy patients but also for other populations receiving immunosuppressive treatments.